Lowe syndrome: a single center's experience in Korea - Hyun-Kyung Kim; Ja Hye Kim; Yoo-Mi Kim; Gu-Hwan Kim; Beom Hee Lee; Jin-Ho Choi; Han-Wook Yoo (Korean Pediatric Society, 2014)
PurposeLowe syndrome is a rare, X-linked recessive disorder caused by mutations in the OCRL gene. It involves multiple anatomic systems, particularly the eyes, central nervous system, and kidneys, and leads to profound growth failure and global developmental delay. This study evaluated the clinical and genetic characteristics of Korean patients with Lowe syndrome.MethodsThe clinical findings and results of genetic studies were reviewed for 12 male patients diagnosed with Lowe syndrome at a single medical institution.ResultsThe mean age of the patients at presentation was 2.2 months (range, 0-4 months), although the diagnosis was delayed by a mean of 2.8 years (range, 0-9.7 years). The mean follow-up period was 9.0 years (range, 0.6-16.7 years). Nine mutations in OCRL were identified in 11 patients (92%), with three novel mutations. The main presentation was congenital cataract in both eyes necessitating early cataract removal in the 11 patients with impaired visual acuity. Profound short stature and developmental delay were observed in all patients, and seizures occurred in 50% of the patients. All patients suffered from proximal renal tubular dysfunction, and one patient developed chronic renal failure. Other manifestations included pathologic fracture (50%), cutaneous cysts (42%), and cryptorchidism (42%). However, there was no bleeding tendency, and none of the patients died during the study period.ConclusionThis study describes the clinical and genetic characteristics of Korean patients with Lowe syndrome. The observations are helpful for understanding the natural courses of Lowe syndrome and for appropriate genetic counseling.